Dementia is Associated With Poorer Quality of Care and Outcomes After Stroke: An Observational Study. (4th June 2020) - Callisaya, Michele L; Purvis, Tara; Lawler, Katherine; Brodtmann, Amy; Cadilhac, Dominique A; Kilkenny, Monique F
Abstract: Background: To determine whether preexisting dementia is associated with poorer quality of care and outcomes after stroke in the acute hospital phase. Method: This was a retrospective analysis of pooled data from the Australian Stroke Foundation national audit conducted in 2015 and 2017. Dementia status was obtained from the medical records. Processes of care to assess quality included: stroke unit care, time-dependent therapy, nursing/allied health assessments, and preparation for discharge. Outcomes included in-hospital complications, independence on discharge, and destination. Logistic regression was used to examine associations between dementia status and processes of care. Multilevel random effects logistic regression, with level defined as hospital, was used to examine associations between dementia status and outcomes. Results: There were 683/7, 070 (9.7%) audited patients with dementia included. Patients with dementia were less likely to be treated in stroke units (58.3% vs 70.6%), receive thrombolysis if an ischemic stroke (5.8% vs 11.1%), have access within 48 hours to physiotherapy (56.4% vs 69.7%) or occupational therapy (46.8% vs 55.6%), see a dietitian if problems with nutrition (64.4% vs 75.9%), or have mood assessed (2.6% vs 12.3%). Patients with dementia were more likely to receive no rehabilitation (adjusted odds ratio 1.88, 95% confidence interval 1.25, 2.83) and be discharged to residential care (adjusted odds ratio 2.36, 95% confidence interval 1.50, 3.72). Conclusion: People with dementia received poorer quality of care and had worse outcomes after stroke. Our findings raise questions regarding equity and the need for better understanding of why the quality of care differs after stroke for people with dementia.